USING DIGITAL STORYTELLING-PHOTOSTORY COMPUTER APPLICATION TO INCREASE THE SPEAKING ABILITY OF THE FIRST YEAR STUDENTS OF SMK DAREL HIKMAH PEKANBARU - Reza, Nove Reza; Azhar, Fadly Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research is to improve the speaking ability of the first year students by using Digital Storytelling-Photostory Computer Application in comprehending the descriptive texts. This is an experimental research with one pre-post test design. The population of the research is the first year students of SMK Darel Hikmah Pekanbaru with 21 samples. To collect the data, the writer administered the pre test, treatments, and the post test at end of the session. In analyzing the data, the t- test formula was used to determine whether the technique applied can significantly increase the students’ speaking ability. From the data collected, it can be seen that the average score of pre test is 64.6. Upon the implementation of digital storytelling, there is a significant increase on students’ scores. It can be seen from the result of post-test. The average score of the post-test is 76.8. The score also reveals that the students have achieved the minimum mastery criteria required by the school. To sum up, digital storytelling-photostory computer application has significantly increase the speaking ability of the first year students of SMK Darel Hikmah Pekanbaru. Keywords: Digital Storytelling, Photostory Computer Application, Speaking Ability, Descriptive Texts